ANALISIS PEMBOROSAN WAKTU KERJA MESIN IS-10 UNTUK PERBAIKAN PROSES PRODUKSI DENGAN METODE PDCA (PLAN, DO, CHECK, ACTION) DI PT GV - Lokaputra, Riduwan; Rosalina, Via; Ariyanto, Darmawan Eko (Jurnal Sains Ilmu Teknologi Industri, 2024)
PT GTR is a manufacturing company with a wire and cable business made from the main material of aluminum and copper materials. PT GV has several targets to achieve optimal company productivity, so that waste elimination is carried out so that there are no obstacles during th This research was conducted by analyzing and streamlining the waste (waste) of the production process using the PDCA (Plan, Do, Check, Action) method by conducting a time study which refers to the SOP (Standard Operating Procedure) as the time standard to be set. This PDCA approach resulted in a solution that to increase production productivity can be done by making standard set up times production process. With the application of the set up time standard, an increase in the percentage of production productivity was obtained, from 3.96% to 7.36%.